Core-shell Powders for Additive Manufacturing of Articles for Underground Construction. (2016) - Bogdanov, Sergey; Sychov, Maxim; Lebedev, Lум; Mjakin, Sergey; Gravit, Marina
Abstract: The article presents the results on the development of core-shell powders for additive manufacturing of articles for underground construction. Core-shell powders were obtained via advanced technologies involving gas (iodide) transport plating of ceramic and carbon materials with metal nanocoatings to improve the target performances (wear- and corrosion resistance, etc.) as well as the 3D simulation and preparation of triply periodic minimal surface (TPMS) structures with specific shapes, including Schoen Gyroid and Schwarz Diamond.